Pedagical enlightenment and natural education in Jean-Jacques Rousseau - Cristiano Eduardo Wendt; Claudio Almir Dalbosco (Universidade Federal de Santa Maria, 2012)
The essay discusses the importance of Jean-Jacques Rousseau for modern pedagogy, by being grounded on his philosophical-pedagogical work Émile or On Education. It seeks to present the meaning of pedagogical enlightenment as well as the concept of natural education, and the two great novelties brought by Rousseau to the educational realm, i.e., the concept of infancy and of education. In this perspective, it analyzes the three main interpretations to which Rousseau's enlightenment was submitted along history: As an optimist of reason, primitivist and dialectician of reason. Assuming the Genevan's thought as a defender of a dialectics of reason, the essay seeks to reflect the unfolding which every concept provokes to its project of natural education and how it reflects in the cognitive and moral development of the infants. At last it deals with the presentation of two innovations which Rousseau brings to the realm of education, the first one which deals with the concept of infancy, and the second one which deals with the pedagogical concept as a whole, by considering the phases of biological, cognitive and moral maturing, where each child is encountered.